2016
DOI: 10.1089/chi.2015.0076
|View full text |Cite
|
Sign up to set email alerts
|

Getting to More Effective Weight Management in Antipsychotic-Treated Youth: A Survey of Barriers and Preferences

Abstract: Background: Mentally ill youth are at risk for developing obesity, especially when they require antipsychotic treatment; moreover, they may face unique challenges in adhering to behavioral weight loss interventions. The aims of this project were to characterize the challenges families of youth with psychiatric disorders face when engaging in weight loss treatment and to gather information on attitudes and preferences for weight management interventions in this population.Methods: We devised a telephone survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Our results suggest adaptations to traditional health coaching delivery models, where existing clinical staff are trained and responsible for implementation, may benefit from the introduction of technology. These results are consistent with previous reports in SMI populations suggesting openness to the use of technology for delivering health behavior change interventions, which have been shown to boost treatment engagement in non-mentally ill obese adults ( 1 , 35 , 36 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results suggest adaptations to traditional health coaching delivery models, where existing clinical staff are trained and responsible for implementation, may benefit from the introduction of technology. These results are consistent with previous reports in SMI populations suggesting openness to the use of technology for delivering health behavior change interventions, which have been shown to boost treatment engagement in non-mentally ill obese adults ( 1 , 35 , 36 ).…”
Section: Discussionsupporting
confidence: 92%
“…Obesity is two to three times more prevalent in people with severe mental illness (SMI), contributing to higher rates of obesity-related conditions like type 2 diabetes and cardiovascular disease (CVD) compared to the general population ( 1 ). This burden of cardiometabolic risk contributes to a 10–15 year mortality gap between those with SMI and the general population ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent visits followed the same format, with the 30-minute discussion including session-specific content (session 2: meal planning and nutrition, session 3: physical activity, and session 4: skills for long-term health behavior change). The order of the content delivered in the sessions was determined based on prior behavioral weight loss treatment development experience in youth and adults with SMI treated in community settings, where qualitative efforts identified the greatest health behavior knowledge and skill deficits in this population were understanding nutrition and healthy meal planning [ 46 , 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…These individuals expressed preferences for digital self-monitoring and support delivered via a mobile device over in-person treatment. Moreover, participants indicated that needs and barriers varied from day to day, and that an intervention adaptive to their dynamically changing needs was important [ 13 ]. As the availability of mobile devices among mentally ill youth increases [ 14 ], this mode of treatment becomes a feasible way to increase access and engagement [ 15 ].…”
Section: Introductionmentioning
confidence: 99%